Lectotype designations taxonomic notes and new synonymies in some species of the bee genus Centris Fabricius, 1804 described by Frederick Smith (Hymenoptera: Apidae) - Vivallo, Felipe (Zootaxa, 2020)
In this paper the primary types of Centris bees described by the British entomologist Frederick Smith deposited in the Natural History Museum, London and in the Oxford University Museum of Natural History, Oxford, United Kingdom were studied. To stabilize the application of some names, lectotypes were designated for C. agilis, C. apiformis (= C. aenea Lepeletier), C. ardens (= C. varia (Erichson)), C. aterrima, C. cineraria, C. concinna (= C. dentata), C. crassipes, C. dentata, C. difformis, C. discolor, C. elegans, C. ephippium, C. festiva, C. ignita (= C. agilis), C. insignis, C. insularis, C. maculifrons, C. melanochlaena, C. mexicana, C. modesta, C. nitida, C. perforator, C. personata (= C. longimana Fabricius), C. plumipes, C. rubella (= C. ferruginea Lepeletier), C. semicaerulea, C. simillima, C. tarsata, C. thoracica (= C. domingensis Dalla Torre) and Anthophora dimidiata (= C. nigerrima (Spinola)). Centris perforator nom. rev. and C. modesta nom. rev. are withdrawn from the synonymy of C. fuscata Lepeletier and C. obsoleta Lepeletier respectively, and consequently revalidated. Centris fulviventris Cresson and C. simillima are removed from the synonymy of C. lanipes (Fabricius), proposing the revalidation of the first species and the second one as its new junior synonym. Centris insignis and C. insignis scutellaris Friese are proposed as new junior synonyms of C. laticincta (Spinola). The critical study of the primary type of C. aterrima, for a long time a misidentified species, allowed for proposing C. anomala Snelling as its new junior synonym. As result of this synonymy, C. apache new species is here described based on specimens incorrectly considered as belonging to C. aterrima. In addition, a lectotype for Centris clypeata Friese (= C. nigrocaerulea Smith) is also designated.